Comparison of Hypomanic Symptoms Between Bipolar I and Bipolar II Disorders: A Network Perspective - Bai, Wei; Feng, Yuan; Sha, Sha; Zhang, Qinge; Cheung, Teris; Zhang, Dexing; Su, Zhaohui; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2022)
Background: Hypomanic symptoms between bipolar-I disorder (BD-I) and bipolar-II disorder (BD-II) are often indistinguishable in clinical practice. This study compared the network structure of hypomanic symptoms between patients with BD-I and BD-II. Methods: The 32-item Hypomania Checklist (HCL-32) was used to assess hypomanic symptoms. Network model was generated in BD-I and BD-II patients. Centrality index of strength was used to quantify the importance of each symptom in the network. The Network Comparison Test (NCT) was used to assess the differences of hypomanic symptoms between BD-I and BD-II patients. Results: Altogether, 423 patients with BD (BD-I: 191 and BD-II: 232) were included. The most central symptom was HCL17 ‘I am more flirtatious and/or am more sexually active’ (strength BD-I =5.21) and HCL12 ‘I have more ideas, I am more creative’ (strength BD-II =6.84) in BD-I and BD-II samples, respectively. The results of NCT showed that four nodes (HCL12 ‘I have more ideas, I am more creative’, HCL17 ‘I am more flirtatious and/or am more sexually active’, HCL23 ‘My thoughts jump from topic to topic’, and HCL31 ‘I drink more alcohol’) were significantly different between the BD-I and BD-II samples. Two edges (HCL3 ‘I am more self-confident’ - HCL17 ‘I am more flirtatious and/or am more sexually active’, and HCL10 ‘I am physically more active (sport etc.)’ - HCL24 ‘I do things more quickly and/or more easily’) were significantly stronger in BD-I compared to BD-II patients. Conclusion: The network structure of hypomanic symptoms is different between BD-I and BD-II patients. Interventions targeting the respective central symptoms and edges should be developed for BD-I and BD-II separately.